Aortic dissection and prophylactic surgery in congenital heart disease. (1st January 2019) - Kuijpers, Joey M.; Koolbergen, Dave R.; Groenink, Maarten; Boekholdt, S. Matthijs; Meijboom, Folkert J.; Jongbloed, Monique R.M.; Hoendermis, Elke S.; Duijnhouwer, Anthonie L.; Mulder, Barbara J.M.; Bouma, Berto J.
Abstract: Background: Proximal aortic dilatation in certain congenital heart diseases (CHD) prompts concerns about dissection and consideration of prophylactic surgery. To evaluate contemporary prophylactic practice, we determined incidence of aortic dissection and prophylactic surgery in aortopathy-associated CHD, compared to Marfan syndrom (MFS) and controls. Methods and results: We followed patients from the CONCOR adult CHD registry (2002–2015), with a native proximal aorta and aortopathy-associated CHD, comprising bicuspid aortic valve/aortic stenosis ('BAV/AS'; n = 2239) and aortic coarctation/conotruncal defects/univentricular heart/ventricular septal defect ('At-risk CHD'; n = 5439). As reference, we selected MFS (n = 356) and 'Control' (atrial septal defect, pulmonary stenosis; n = 2940) patients. Cumulative incidences of dissection and prophylactic proximal aortic replacement – considered competing events – were determined, and compared corrected for age and sex. Median follow-up was 6.7 years. Ten-year dissection-incidence was 0.3% (95%CI: 0.0–0.7) in BAV/AS and 0.2% (0.0–0.3) in At-risk CHD, both significantly lower than in MFS (4.1%; 1.8–6.4) and similar to Controls (0.1%; 0.0–0.3). Ten-year prophylactic-surgery incidence was 9.3% (7.6–11.0) in BAV/AS and 0.7% (0.5–1.0) in At-risk CHD, both significantly lower than in MFS (21.3%; 16.3–26.3) and higher than in Controls (0.1%; 0.0–0.3). Conclusions: In contemporary practice, aortic-dissection incidence is low in adults with aortopathy-associated CHDs, while prophylactic-surgery incidence is high in BAV/AS. To reduce surgical burden, BAV/AS patients could benefit from more individualised prophylactic-surgery algorithms. Highlights: In adults with aortopathy-associated congenital heart disease, aortic dissection risk was lower than in Marfan syndrome. Prophylactic aortic replacement was frequent in bicuspid aortic valve/aortic stenosis, not in other congenital heart disease. Many prophylactic aortic replacements in bicuspid aortic valve/aortic stenosis were performed with aortic valve replacement. Patients with bicuspid aortic valves may benefit from individualised algorithms, to target prophylactic aortic replacement.